Supporting knowledge transfer for low vision interventions through an online directory of validated assessment tools - Wittich, Walter; Houtekier, Catherine; Cantin, Sylvie (Canadian Journal of Optometry, 2021)
[please note that we have not provided an abstract, given the short communication nature of the text]